A cross-sectional study on solid oral dosage form modifications among older patients admitted to a Malaysian teaching hospital - Razak, Nur Nabiha; Sha'ari, Mohamad Suhaidi; Jamludin, Nurul Ashikin; Akkawi, Muhammad Eid; Jamal, Janattul AIn; Abd Wahab, Mohd Shahezwan (International Islamic University Malaysia, 2025)
INTRODUCTION: Older adults often require multiple medications, increasing their risk of polypharmacy and drug-related problems (DRPs). Solid oral dosage forms (SODFs) are the most common medication formulation used by patients. However, administering SODFs to older adults can be challenging, especially for those with swallowing difficulties, leading to practices such as crushing, splitting tablets, or opening capsules. These modifications can affect medication efficacy and safety. This study aims to examine the prevalence of SODF modification among hospitalized older adults, the methods used, the reasons for modification, and the appropriateness of these practices. MATERIALS AND METHOD: This cross-sectional study included patients aged 60 years and above admitted to the general medical ward of a tertiary teaching hospital. Eligible participants were identified through the hospital's electronic registration system. Sociodemographic and clinical data were collected using a standardized form. Participants were interviewed about their SODF modification practices, and swallowing difficulties were assessed using the PILL-5 questionnaire. RESULTS: Of 122 participants, 54.1% were aged 60–69, and 9.8% reported dysphagia. SODF modification was practiced by 55.7%. Swallowing problems and pill dysphagia are significantly associated with SODF modification. Among those modifying SODFs, 47.1% incorrectly believed all medications could be safely altered. Splitting tablets was the most common practice (92.6%). CONCLUSION: Both dysphagia and pill dysphagia are significantly associated with SODF modification practices among older patients. Healthcare providers should be vigilant about these practices in older patients with swallowing difficulties. Proper education and assistance in medication handling are essential for this population.